Pattern of Electroencephalography in Recurrent Febrile Seizure Patient - Adinda Chairunnisa; Prastiya Indra Gunawan; Isti Suharjanti (Health Notions, 2019)
Background: Febrile seizures are seizures that often occur in children, usually of a non-hazardous nature and do not have a prolonged effect. Febrile seizures most often occur in children under five years of age and are reported to occur in 2-5% of the pediatric population. Febrile seizures are categorized as simple, complex and plus febrile seizures. In some patients, EEG is needed to ascertain whether a true febrile seizure occurs. Objective: This study aims to determine the EEG pattern in recurrent febrile seizure patients at the Child Inpatient Installation of Dr. Soetomo Surabaya. Method: This study used a retrospective descriptive method with medical record instruments. Results: This study showed that of 46 recurrent febrile seizures, only 21 patients could see the EEG results. Of the 18 patients with complicated febrile seizures there were 27.78% abnormal and 72.22% normal. One simple febrile seizure patient obtained a normal EEG result. Of the two patients with febrile seizures plus 50% abnormal results and 50% normal results. Conclusions: The EEG pattern in patients with recurring complex febrile seizure obtains the most abnormal result. Keywords: recurrent febrile seizure; electroencephalography; prevalence